2015
DOI: 10.1039/c4nr05061d
|View full text |Cite
|
Sign up to set email alerts
|

Size dependent biodistribution and toxicokinetics of iron oxide magnetic nanoparticles in mice

Abstract: In spite of the immense benefits from iron oxide magnetic nanoparticles (IOMNs), there is scanty information regarding their metabolic activities and toxicity in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
111
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(126 citation statements)
references
References 52 publications
(105 reference statements)
11
111
0
Order By: Relevance
“…Differences in the biological properties of nano-Fe for particles of different sizes have been demonstrated previously (Yang et al, 2014). Decreasing Fe particle size has been reported to increase the absorption of this element (Rohner et al, 2007), and size-dependent toxicity has been demonstrated (Cho et al, 2009;Prietl et al, 2014).…”
Section: Introductionmentioning
confidence: 85%
“…Differences in the biological properties of nano-Fe for particles of different sizes have been demonstrated previously (Yang et al, 2014). Decreasing Fe particle size has been reported to increase the absorption of this element (Rohner et al, 2007), and size-dependent toxicity has been demonstrated (Cho et al, 2009;Prietl et al, 2014).…”
Section: Introductionmentioning
confidence: 85%
“…The momentum force is stronger in larger particles, which lead to a high probability of wall collision and rapid clearance by mononuclear phagocytic system [38,45]. In an in vivo study, various sizes of IONPs (diameters of 10, 20, 30 and 40 nm) were delivered into mice to determine biodistribution and systemic toxicity [46]. Results showed the highest uptake of the smallest nanoparticles (10 nm) into the liver, while the spleen had the highest uptake of the largest nanoparticles (40 nm).…”
Section: Sizementioning
confidence: 99%
“…The majority of published studies show that smaller IONPs are more toxic. 26,27 Indeed, smaller diameters are associated with higher surface area and, consequently, more rapid pattern of Fe 3+ release with associated oxidative burst. However, this study demonstrated that smaller bare IONPs were less toxic compared to SiO 2 -containing IONPs with larger diameters.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, 3-aminopropyltrimethoxysilane (APTMS)-coated IONPs were shown to have greater negative impact on viability of fibroblasts and fibrosarcoma cells as compared to bare IONPs and IONPs shielded with TEOS or TEOS/APTMS. 27 Another study explored the effects of bare or oleate-covered IONPs on human lymphoblastoid TK6 cells and primary blood cells. 17 Surprisingly, oleate-coated IONPs possessed dose-dependent cyto-and genotoxicity whereas bare IONPs were nontoxic at the equivalent dose.…”
Section: Discussionmentioning
confidence: 99%